Nekaj nesistematičnih pogledov na sistem sodobne koroške slovenske literature - Leben, Andrej (Jezik in slovstvo, 2014)
As a literary historian, an author of scientific discussions and essays, a lecturer at various symposiums and (people's) universities, and an author of radio and theatre plays with Carinthian topics, Prof. Matjaž Kmecl has made an essential contribution to the visibility and knowledge of Carinthian Slovenian literature. Today, the literature created at the crossroads of the Slovenian and Austrian or German literary (poly)system displays an inner differentiation and can be treated as part of a special literary subsystem established by the network of specific inter-systemic intra- and interrelations.
Keywords: Kmecl, Matjaž, 1934-; Slovene literature; slovenska književnost; slovenska zamejska književnost; Koroška; literarni sistemi; slovenski literarni zgodovinarji